Mode of presentation of abdominal tuberculosis (Bangladesh Medical Journal Khulna, 2013)
This study included 32 female and 20 male patients. Varied presentation of abdominal tuberculosis included pain in abdomen (95%), fever (84.6%), weight loss (88%) and mass in abdomen. Laparoscopic and open adhesiolysis (18.75%) resection and anastomosis (12.5%), stricturoplasty (12.5%), loop ileostomy (25%), closure of perforation (18.75%) and limited right hemicolectomy (12.5%) were the procedures carried out. Two patients expired with a mortality rate of 4%. The diagnosis of abdominal tuberculosis is difficult due to lack of specific signs and symptoms. However predetermined clinical assessment can be readily applied for earlier diagnosis. Surgical exploration is reserved for equivocal cases and for those who present as emergencies. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13637 Bang Med J (Khulna) 2012; 45 : 3-5